SISTEM PAKAR DIAGNOSA PENYAKIT IKAN KOMET MENGGUNAKAN FORWARD CHAINING - Sandy Kosasi (Teknik Informatika Universitas Malikussaleh, 2014)
Diagnosis is an early stage used to know the symptoms carassius auratus suffers; therefore, the diseases can be healed. The aimof this research is to create an expert systemapplication relating to fishery, especially in the diseases carassius auratus suffers. The existence of an expert system use to diagnose carassius auratus can provide a lot of easiness for anyone who wants to cultivate or just keep it. The design of expert system application uses prototype method whereas forward chaining is applied by using inference method. Forward chaining method begins with premises or input information (if) first and continued by conclusion (then). The expert system application of carassius auratus disease diagnosis can save the users’ cost. Users who have an access right as an administrators can add, change, or delete the data of symptoms, pests and diseases, and solutions therefore the system can keep developing. To obtain a more accurate results, we can combine it with CF (Certainty Factor) theorem.